Equine severe combined immunodeficiency - Lund, Louise (SLU/Dept. of Animal Breeding and Genetics (until 231231), 2007)
Severe Combined Immunodeficiency (SCID) is a disease with a genetic background in Arabian horses and crossbreeds with Arabians. The disease has been known and documented since the 1970's and was early suggested to have an autosomal recessive mode of inheritance.